Efficient gingival health screening using biofluorescence of anterior dental biofilms - Hyo-Jung Kim; Eun-Song Lee; Baek-Il Kim (Photodiagnosis and Photodynamic Therapy)
Purpose: In study, we aimed to evaluate the biofluorescence of anterior dental biofilms using Quantitative Light-induced Fluorescence (QLF) technology to screen for gingival health. Methods: Fifty-five (n = 55) adult participants aged ≥ 20 years with gingivitis were included in this study. Fluorescence images of the upper and lower anterior teeth were obtained using Qraycam Pro, a device based on the QLF technology. To evaluate the biofilm fluorescence deposition level, the percentage of the dental biofilm area detected using red biofluorescence was calculated relative to the total surface area of the anterior teeth. To evaluate the gingival health status, the Silness-Lӧe plaque index (PI), Lӧe -Silness gingival index (GI), and bleeding-on-probing index (BOP) were assessed. Pearson's correlation and logistic regression analyses were performed to examine the relationship between biofilm biofluorescence and the gingival health status. Results: The group with the larger fluorescent biofilm area exhibited significantly higher GI and BOP values (p < 0.05) than the group with the smaller fluorescent biofilm area. Furthermore, significant correlations were found between the fluorescent biofilm area and GI, BOP, and PI (r = 0.422, r = 0.376, and r = 0.499, respectively; p < 0.05). Logistic regression analysis adjusted for sociodemographic variables, smoking, and alcohol consumption showed that the odds ratio for moderate gingivitis in the group with a larger fluorescent biofilm area was 6.07 compared with that in the group with a smaller area (p < 0.05). Conclusion: Evaluating the biofluorescence of anterior dental biofilms using QLF technology is an effective indicator for screening gingival health and identifying individuals at a high risk for gingivitis.